Fresh water (Earth & space science course)
Sail through Earth's fresh water supply and differentiate between sources of fresh water on Earth's surface and below ground. Investigate networks of streams and rivers, the different stages of river development, and how rivers reshape Earth's surface through erosion and deposition. Students will soak up ways in which fresh water is used and polluted, and identify methods to conserve this vital resource.